Strategy to develop the production of texts in students of a higher Education Institute in Lima: - Canchanya Ayala, Alfredo (2023)
The research proposes the design of a methodological strategy to optimize the production of texts in the students of the Written Communication course of the first cycle of a higher education institute in Lima. This is framed within the interpretive and socio-critical paradigms, with a qualitative approach, the type of research is applied educational. The sample is 70 students and three teachers. Among other techniques, the survey, the observation and the interview were used, and among the instruments the pedagogical test for the students, the questionnaire, the observation guide and the interview guide were used. The most important result is the design of a methodological strategy to optimize the production of texts that allows students to go through the stages of sensitivity, pre-writing, writing and post-writing; These being supervised by the teacher, following indications for their practice. It ends by concluding that the study exhibits a solid approach that will change the teacher's practice and develop a better production of texts in students.